The impact of emotional intelligence towards relationship of personality and self-esteem at workplace - Johar, Siti Sarawati; Mad Shah, Ishak; Abu Bakar, Zainudin (Elsevier Science Ltd, 2012)
Leader personality in dimensions of industrial and organizational psychology research has given attention because it was detected can influence the leader behavior, which is also as a manager or supervisor in an organization. In this study, the issue in the workplace is referring to the personality and emotional intelligence of leaders, and self-esteem of employees. The main purpose of this study was to identify the impact of mediators that can influence the relationship between the personalities of the leader with the self-esteem of employees. A total of 285 civil servants in the Local Authority (PBT) have been selected as respondents. Measurement equipment used in data collection involves the Leader Personality Questionnaire, Leader Emotional Intelligence Questionnaire and Employee Selfesteem Questionnaire. The data were analyzed using descriptive and inferential analysis including such as correlation, regression simple and hierarchical regression. The findings indicate that emotional intelligence of leader has the impact on the relationship between leader personalities with self-esteem of employees. It also explained that the elements of emotional intelligence competencies play a significant role as mediators that influence the relationship between the leader personalities and employees self-esteem. The most important findings are when personalities of leaders will be more dynamic and robust when there are emotional intelligence elements.